Implications of the 375W mutation for HIV-1 tropism and vaccine development - Verdejo-Torres, Odette; Vargas-Pavia, Tania; Clapham, Paul R.; Dueñas Decamp, Maria José; Syeda, Fatima (ASM, 2025)
Understanding how different amino acids affect the HIV-1 envelope (Env) trimer will greatly help the design and development of vaccines that induce broadly neutralizing antibodies (bnAbs). A tryptophan residue at position 375 that opens the CD4 binding site without modifying the trimer apex was identified using our saturation mutagenesis strategy. 375W was introduced into a large panel of 27 transmitted/founder, acute stage, chronic infection, and AIDS macrophage-tropic and non-macrophage-tropic primary envelopes from different clades (A, B, C, D, and G) as well as complex and circulating recombinants. We evaluated soluble CD4 and monoclonal antibody neutralization of WT and mutant Envs together with macrophage infection. The 375W substitution increased sensitivity to soluble CD4 in all 27 Envs and macrophage infection in many Envs including an X4 variant. Importantly, 375W did not impair or abrogate neutralization by potent bnAbs. Variants that were already highly macrophage tropic were compromised for macrophage tropism, indicating that other structural factors are involved. Of note, we observed a macrophage-tropic (clade G) and intermediate macrophage-tropic (clades C and D) primary Envs from the blood and not from the central nervous system (CNS), indicating that such variants could be released from the brain or evolve outside the CNS. Our data also indicate that ¿intermediate¿ macrophagetropic variants should belong to a new class of HIV-1 tropism. These Envs infected macrophages more efficiently than non-macrophage-tropic variants without reaching the high levels of macrophage-tropic brain variants. In summary, we show that 375W is ideal for inclusion into HIV-1 vaccines, increasing Env binding to CD4 for widely diverse Envs from different clades and disease stages.